The bus rapid transit (BRT) in Dar es Salaam: A pilot study on critical infrastructure, sustainable urban development and livelihoods - Krüger, Fred; Titz, Alexandra; Arndt, Raphael; Gross, Franziska; Mehrbach, Franziska; Pajung, Vanessa; Suda, Lorenz; Wadenstorfer, Martina; Wimmer, Laura (Sustainability, 2021)
Inner-city transportation looms large in big cities in the so-called Global South due to rapid population and urban growth. To tackle this challenge, a Bus Rapid Transit (BRT) system was implemented in Dar es Salaam (Tanzania) in 2016. This paper reports on the results of a pilot study on the impacts of the BRT on city development and livelihoods in Dar. Our pilot study, which is part of the collaborative research project LIPSINDAR (Linking Partners for a Sustainable and Inclusive Dar es Salaam), was not designed to provide a comprehensive insight into the problems of urban planning, infrastructure modification and their impact on urban livelihoods. Rather, using the example of Dar es Salaam, the study served as an entry point to highlight challenges and future research demands in the context of urban insecurities and risks in large cities of the Global South. In particular, our study investigated the BRT as an element of critical infrastructure in Dar es Salaam and probed into its impact on residents’ livelihoods, focusing on the influence of service disruptions on everyday routines, and on different stakeholders’ views on the functionality of the BRT. Elaborating on this topic, interviews, street vendor surveys and mappings were used as methods to describe the processes. To examine the results more closely, the outcome was divided into groups of different fields of activity, namely Traffic Management, Local Residents, City Administration, Basic Provision Services and Street Vendors. In summary, the pilot study confirms that the implementation of the BRT system has, in general, served to improve urban livelihoods. Reducing commuting times and enhancing access to basic services found positive results. There is, however, still potential for improvement: the bus network, in particular, needs to be expanded and the vulnerability to natural extreme events, especially flooding, needs to be addressed.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Critical infrastructure; Criticality; Eastern Africa; Inclusiveness; Infrastructure; Livelihoods; Risk; Society; Sub-saharan Africa; Sustainability; Transportation; Urban resilience